Ujamaa and the Role of Moral Integrity in African Socio-Political Leadership - Waitherero, Simon Njuguna (International Journal of Culture and Religious Studies, 2023)
This paper seeks to communicate the roles played by Ujamaa in impacting moral integrity on social political leadership in Africa. Ujamaa spirit appears to be one of the key component of leadership amongst African leaders as proposed by Julius Nyerere. This paper seeks to further analyse how Julius Nyerere applied Ujamaa philosophy in Tanzania and the associated fruits of the application.